Senegal : Second Review Under the Third Annual Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Performance Criteria, and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper assesses Senegal's Second Review Under the Third Annual Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Requests for Waiver of Performance Criteria. The authorities indicated that policies for the period ahead aimed at reducing poverty and maintaining macroeconomic stability, while pressing forward with structural reforms to enhance growth prospects. IMF and the World Bank staff have urged the authorities to take a cautious approach to undertaking a package of large infrastructure projects under consideration to ensure their economic viability and minimize any fiscal costs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet